Practice and thinking on the construction of PICC nursing clinic in the Traditional Chinese Medicine hospital (中医医院PICC护理门诊建设实践与思考) - XU Zhe (许哲); ZHAO Nan (赵楠); XU Wei (胥微); ZHAO Jingtao (赵静涛) (中西医结合护理)
This article explores the construction plan and innovative operation mode of Peripherally Inserted Central Catheter (PICC) nursing clinics in a certain Traditional Chinese Medicine(TCM) hospital, and to evaluate its practical effects. The PICC nursing clinic had a reasonable layout, and the work was carried out through the formation of intravenous treatment teams, establishment of rules and regulations, nursing expert preparation system, multi-disciplinary team cooperation system, special quality control of outpatient clinics, application of characteristic Chinese Medicine technology, and networked nursing guidance, etc. (本文探讨了中医医院PICC护理门诊的建设方案和创新运行模式, 并评价其实践效果。PICC护理门诊设置布局合理, 通过组建静脉治疗团队, 通过建章立制、护理专家备班制、多学科团队合作制、门诊专项质量控制、应用中医特色技术及网络化护理指导等形式开展工作。)